Voice Rehabilitation after Total Laryngectomy in TUTH - Bhandari, R; Rayamajhi, P; Baskota, DK; Pradhan, kR (Nepalese Journal of ENT Head and Neck Surgery, 2011)
Key words: Esophageal voice; Total Laryngectomy; rehabilitation DOI: 10.3126/njenthns.v1i1.4731 Nepalese J ENT Head Neck Surg Vol.1 No.1 (2010) p.14-16